Kinerja Kesehatan Bank Pembangunan Daerah Indonesia Dengan Chow Test dan Hausman Test - Yusnita Octafilia; Putu Rani Susanthi; Evelyn Wijaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Regional Bank is a commercial bank whose shares owned by the provincial government. So that, the Regional Bank plays indirectly a very large role in regional development. However, these Regional Banks have not contributed significantly to the development of their respective regions. From this description, this study aims to analyze the health performance of Regional Banks after the global economic crisis in 2008 using the Chow Test and the Hausman Test. This study has a population of 26 Regional Banks and a sample of 25 banks which are selected using purposive sampling. The result showed that from their financial ratios, Regional Banks tend to be in very healthy condition. Based on the research period from 2009 to 2019, the Regional Banks also shows results that tend to be very healthy. In terms of financial ratios and research period, the Loan to Deposit ratio tends to show fairly healthy results. Both of these results are supported by adjusted R2 using the Chow Test and Hausman Test of 0.86 which means that all of these financial ratios have an effect of 86% with details that Capital Adequacy Ratio, Net Performing Loan, Net Interest Margin, and Loan to Deposit Ratio has a significant positive effect, while Return on Equity has positive and insignificant effect and Operational Cost of Operating Cost of Operating Income has a significant negative effect on Return on Assets. Keywords: Regional Banks, Capital Adequacy Ratio, Non-Performing Loan, Return on Assets, Return on Equity, Net Interest Margin, Operational Cost of Operating Income, Loan to Deposit Ratio, Chow Test, and Hausman Test.